ANALISIS PENGELOLAAN AREA PARKIR KENDARAAN UNTUK MENDUKUNG EFISIENSI OPERASIONAL SISI DARAT DI BANDAR UDARA SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Muhammad Bagas Dirgantara; Ubaedillah; Arnas, Yenni (FTK UNSURYA, 2025)
The trend of increasing vehicle volume entering the Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan Airport area has increased. However, in actual implementation, airport parking management still faces a number of challenges, namely the lack of maximum utilization of parking capacity, resulting in many drivers choosing to park in the drop zone area. This causes the drop zone area to be less conducive and often leads to traffic congestion in that area. This study aims to analyze parking management and provide strategic recommendations to improve the operational efficiency of airport parking. This study employs a qualitative descriptive method. The results of data collection through observation, interviews, documentation, and questionnaires reveal issues in parking area management that are not yet optimal, such as waterlogging, non-functional facilities, and confusing signage for passengers. The limited accessibility of the parking building makes it an unattractive option for vehicle users. The lack of discipline among vehicle users is also a major factor contributing to congestion in the drop-off zone. Regression analysis results also indicate a significant influence between parking management and operational efficiency on the ground side.